THE EFFECT OF THE FLICT MODEL ON BIOLOGY STUDENTS' HIGHER-ORDER THINKING SKILLS IN AN ANIMAL ECOLOGY COURSE - Panggih Priyambodo; Median Agus Priadi (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2026)
Students’ mastery of Higher Order Thinking Skills (HOTS) remains suboptimal. A new instructional model, the Flipped Learning Model with Case-based Tournament (FliCT Model), has been expert-validated to facilitate improvements in students’ HOTS. The FliCT Model integrates the principles of the case-based method and Team Games Tournament within a flipped learning framework. This study aims to examine the effectiveness of the FliCT Model on a limited scale in improving HOTS-domain learning outcomes among undergraduate students of the Biology Education program. A total of 34 undergraduate students from the Biology Education Study Program, Faculty of Teacher Training and Education, Universitas Lampung, enrolled in Animal Ecology courses, participated in this pre-experimental study with a one-group pre-test–post-test design. The research data were collected using a validated instrument for the HOTS domain cognitive learning outcome test, which includes aspects of analyzing, evaluating, and creating. The data analysis used was the Wilcoxon test and the N-Gain test. The model design validation confirmed that the FliCT Model is highly valid (88.6). The Wilcoxon test indicated a significant improvement in students’ HOTS-domain learning outcomes after the implementation of the model (p<0,05), while the N-gain analysis showed a moderate level of improvement (0.49). These results demonstrate the effectiveness of the FliCT Model in enhancing students’ HOTS, particularly critical thinking, through the integration of case-based, competitive, and collaborative activities within a flipped learning framework. Further large-scale studies are required to establish the generalizability of these findings.